DNA swivel enzyme activity in a nuclear membrane fraction. - Yoshida, S (1977)
DNA swivel (nicking-rejoining) enzyme activity has been studied in various cell fractions of a human lymphoid cell line. Swivel activity is found only in chromatin and in a nuclear membrane fraction containing DNA and possessing endogenous DNA synthesizing activity. Twenty percent of the total swivel activity and less than one percent of the total DNA are in the membrane fraction. The swivel enzyme is more tightly bound to the membrane fraction than to the chromatin fraction. These observations suggest that the swivel enzyme may be a replication factor, specifically bound to replicating DNA in the membrane fraction.